Special report. Managed care's impact on radiologic science education. - Dowd SB; Tilson ER (Radiologic Technology)
This special report describes the results of an ASRT-commissioned opinion survey of radiologic science program directors to gauge the estimated impact of managed care on radiologic science education. Specific topics explored include the effect of managed care on clinical education, student applications, finances and education. Comparisons were made by institution (hospital, associate and baccalaureate degree) and by discipline. Although the opinions of program directors suggest that managed care has impacted radiologic science education, it cannot be isolated as the causative factor. Also, programs do not appear to be meeting the educational desires of managers for new graduates, as described in several other studies.